2015
DOI: 10.1111/cch.12292
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anxiety versus depressive disorders: specific relations to infants' crying, feeding and sleeping problems

Abstract: Primiparous mothers with anxiety disorders may be more prone to anxious misinterpretations of crying and feeding situations leading to an escalation of mother-infant interactions. The relation between maternal depressive and infant sleeping problems may be better explained by a transmission of unsettled maternal sleep to the fetus during pregnancy or a lack of daily structure and bedtime routine with the infant. Maternal disorders prior to pregnancy require more attention in research and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
6
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 66 publications
1
80
6
8
Order By: Relevance
“…On the theoretical side, the association between excessive infant crying and maternal depression and anxiety is well known, but there is little consensus about the direction of causation. For example, a recent study 27 concluded that maternal anxiety during pregnancy predicted excessive infant crying. The present study was not designed to provide causal information and the absence of a control group, in particular, prevents a conclusion regarding whether the reductions in parental anxiety and depression that were observed between baseline and outcome measurements were attributable to the study's parental support package, to reductions in infant crying that would be expected with infant development or to the passage of time.…”
Section: Outcome Measures and Changes Since Baselinementioning
confidence: 99%
See 1 more Smart Citation
“…On the theoretical side, the association between excessive infant crying and maternal depression and anxiety is well known, but there is little consensus about the direction of causation. For example, a recent study 27 concluded that maternal anxiety during pregnancy predicted excessive infant crying. The present study was not designed to provide causal information and the absence of a control group, in particular, prevents a conclusion regarding whether the reductions in parental anxiety and depression that were observed between baseline and outcome measurements were attributable to the study's parental support package, to reductions in infant crying that would be expected with infant development or to the passage of time.…”
Section: Outcome Measures and Changes Since Baselinementioning
confidence: 99%
“…For instance, parental characteristics, such as depression, anxiety and high levels of arousal, have been found to influence how parents interpret and respond to infant crying. [25][26][27][28] Social isolation, although less studied, may also increase its impact. The implication for clinical practice is that assessments need to take account of parental vulnerabilities and supports, as well as infant crying.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…Colic is more common among first-borns, most likely because first-time parents are more anxious than parents of subsequent children (Ståhlberg 1984). While biologic mechanisms may play a role in some cases of infantile colic (Szajewska et al 2013), behavioural and psychosocial mechanisms also appear relevant (Wolke et al 1994, Keefe et al 2006, van Sleuwen et al 2006, Blom et al 2009, Howell et al 2009, Newnham et al 2009, Petzoldt et al 2016. Many studies have focused on the association between psychosocial factors measured during pregnancy such as prenatal maternal depression, anxiety and low social support, as well as prenatal paternal depression and newborn colic or crying or fussiness (Rautava et al 1993, Canivet et al 2005, van den Berg et al 2009, Petzoldt et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…A crying baby requiring increased attention of the mother contributed to the development of psychological problems in the women in our study. Similarly, Petzoldt et al (2016) found a correlation between anxiety and depressive disorders of mothers and breastfeeding problems, crying babies and babies with sleep disorders. The research led by Kumwar et al (2015) proved an association between the child's health problem and postnatal depression, but this was not confirmed in our study.…”
Section: Discussionmentioning
confidence: 87%